KONSEP AKHLAK IMAM AL GHAZALI - Mohd Aji Isnaini (Wardah, 2011)
Surely I was sent to perfect morals, Rasulullahn hadith illustrates how important it is morality that must-have for the survival of God on earth, the definition of morality according to al-Ghazali was "The phrase about living conditions in the soul, where all behavior stems from it with great ease without requires a process of thought and contemplation. Described good character if his mental condition into the source of good deeds, both in mind and the Shari'a. So conversely the bad deeds as well as violate the Shari'a is the moral condition of the poor. There are four elements that a good moral standards when these four elements are balanced so well that moral science, emotions, lust and fair.The theory of the method to educate the moral, as the expression of al-Ghazali. Normality on the moral health of the soul, and a tendency to stay away from normality is a disease or disorder.Thus, the antidote is Mujâhadah and Riyâdhatun Nafs as a way to treat it is to educate morality, by doing good deeds-deeds required by morality by improving life is to eliminate the various evil and bad morals, and won a moral virtue, good character, as how to treat limb pain is to eliminate the disease and seek recovery.